The diversification of tourism space in Central Pomerania - Rydz, Eugeniusz (Turyzm/Tourism, 2014)
The paper presents issues of the formation and diversification of the Central Pomeranian tourism space. The author conducted an analysis of tourism accommodation facilities and tourism assets, which allowed him to identify a number of functional subspaces within the Central Pomeranian tourism space. Particular attention was paid to recreational tourism in coastal and lake areas, as well as to selected aspects of agritourism and the role of spas in Central Pomerania.